Computational Fluid Dynamics Analysis of Substrate Surface Energy and Ink Surface Tension Effects on Deposition of Conductive Ink - Salik, Muhammad Nauman; Loo Yuen Hern; Khirotdin, Rd. Khairilhijra’; Nurhaffizah Hassan; Muhamad Syarifuddin Mohd. Yasin (International Journal of Integrated Engineering, 2025)
Precise control of conductive ink deposition remains challenging in printed electronics manufacturing, where substrate variability significantly impacts pattern fidelity and electrical performance. This investigation comprehensively examines how substrate surface energy (SSE) and ink surface tension (ST) interactions govern the formation of line width through integrated computational-experimental methodology. Using Ansys Fluent with enhanced Volume of Fluid modelling, seventeen substrate materials covering surface energies from 16.49 to 65.39 mJ/m² were analysed to establish quantitative deposition relationships. The computational framework incorporated a modified formulation accounting for contact angle dynamics and substrate-specific wetting behaviour. Silver conductive ink particles were deposited via controlled droplet methodology to isolate surface energy effects from dispensing variables. Results demonstrate 87.9% variation in line width across the investigated spectrum, with optimal deposition occurring within a narrow SSE range of 40-45 mJ/m². FR4 substrates achieved target line widths with minimal deviation (+2.3%), while ceramic materials exceeded targets by up to 53.8%. The enhanced model exhibited a substantial reduction in prediction error compared to conventional approaches, particularly within the optimal surface energy window, where errors remained below 6%. These findings provide manufacturers with actionable guidelines for substrate selection and surface treatment optimization, challenging current quality control paradigms while offering pathways toward more predictable, sustainable manufacturing processes in aerospace structural health monitoring and precision electronics applications.